EXAMINING THE FACTORS THAT LED TO THE REVOLUTION IN THE COUNTRIES THAT WERE ELIMINATED AT BUMN - Mercy Monika R Sitompul; Runtung Sitepu; Faisal Akbar; Ningrum Natasya Sirait (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
Separated state wealth has been a "sexy" topic for additional research ever since Law No. 17 of 2003 on State Finances was created, specifically article 2 letter g, which declares that separated state wealth is under the purview of State Finance. This article is cited by all parties when discussing issues pertaining to the riches of divided nations. Act No. 17 of 2003, however, does not specify what constitutes the wealth of a divided state, how it functions, how it is supervised, or how it reports on its obligations. This paper will explain that even though the wealth of the separated state is included in the scope of the state's finances does not mean that the entrepreneur and his responsibilities follow the APBN mechanism and also respond to the cause of the occurrence of differences of opinion. This research is carried out using a method of normative jurisprudence, which is to test and study secondary data. Using secondary information such as legislative regulations, court decisions, legal theory and expert opinion to obtain clarity on the problem. The study concluded that the law was not intended to regulate the wealth of the separated state, and differences of opinion were due to a misunderstanding of the scope of the state's finances and attached the status of state organizer to the body of BUMN